Severe mental illness and induction of labour: outcomes for women at a specialist antenatal clinic in Western Australia - Frayne, Jacqueline; Lewis, Lucy; Allen, Suzanna; Hauck, Yvonne; Nguyen, Thinh (Wiley-Blackwell Publishing Asia, 2013)
Background: Limited evidence is available around induction of labour (IOL) and obstetric outcomes for pregnant women with severe mental illness (SMI).Aims: Our study examined obstetric and neonatal outcomes for women attending a specialist childbirth and mental illness (CAMI) antenatal clinic in Perth, Western Australia (WA), who experienced or did not experience IOL. Methods: A retrospective study was conducted between December 2007 and May 2012 (n = 222), using patient records and computerised perinatal data collected by the Obstetrics and Gynaecology Clinical Care Unit. Descriptive statistics and univariate comparisons using Mann–Whitney tests and X2 tests were conducted using SPSS. Results: The overall rate of IOL in this study group was 40%, which was significantly higher than the WA Mother Baby Statistics by 11.6% (95% CI 4.9–18.3%, P < 0.002). Of those induced, 30% (27 of 185) were induced for psychiatric reasons. Women with schizophrenia were more likely to have IOL for an obstetric/fetal reason than a psychiatric reason (45% vs. 15%, P = 0.051). Women who experienced an IOL were less likely to have a spontaneous vaginal delivery (SVD) and more likely to have an assisted vaginal birth or emergency caesarean section (P = 0.040). Irrespective of labour onset, special care nursery admission (SCN) rates were similar and high for both groups (36% vs. 32%, P = 0.599). Conclusion: Obstetric management for women with SMI is complex, and psychiatric factors as well as medical factors must be considered to ensure the best outcomes for mother and infant.